Social Experience Does Not Abolish Cultural Diversity in Eye Movements - Kelly, David J.; Jack, Rachael E.; Miellet, Sebastien; De Luca, Emanuele; Foreman, Kay; Caldara, Roberto (Frontiers in Psychology, 2011)
Adults from Eastern (e.g., China) and Western (e.g., USA) cultural groups display pronounced differences in a range of visual processing tasks. For example, the eye movement strategies used for information extraction during a variety of face processing tasks (e.g., identification and facial expressions of emotion categorization) differs across cultural groups. Currently, many of the differences reported in previous studies have asserted that culture itself is responsible for shaping the way we process visual information, yet this has never been directly investigated. In the current study, we assessed the relative contribution of genetic and cultural factors by testing face processing in a population of British Born Chinese (BBC) adults using face recognition and expression classification tasks. Contrary to predictions made by the cultural differences framework, the majority of BBC adults deployed ‘Eastern’ eye movement strategies, while approximately 25% of participants displayed ‘Western’ strategies. Furthermore, the cultural eye movement strategies used by individuals were consistent across recognition and expression tasks. These findings suggest that ‘culture’ alone cannot straightforwardly account for diversity in eye movement patterns. Instead a more complex understanding of how the environment and individual experiences can influence the mechanisms that govern visual processing is required.